2018
DOI: 10.1016/j.tranon.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Proteomic Investigation of Circulating Exosomes and Discovery of Biomarkers Associated with the Progression of Osteosarcoma in a Clinical Model of Spontaneous Disease

Abstract: Circulating cancer exosomes are microvesicles which originate from malignant cells and other organs influenced by the disease and can be found in blood. The exosomal proteomic cargo can often be traced to the cells from which they originated, reflecting the physiological status of these cells. The similarities between cancer exosomes and the tumor cells they originate from exhibit the potential of these vesicles as an invaluable target for liquid biopsies. Exosomes were isolated from the serum of eight osteosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…As far as EV-associated proteins are concerned, circulating levels of EV-associated TGF-β have been found to be increased in osteosarcoma patients, when compared to healthy control subjects (27). A proteomic investigation of circulating EVs in canine serum samples identified EV related proteins useful to distinguish serum of osteosarcoma from serum of healthy or fractured dogs (72). Furthermore, Brady et al identified two proteins associated with EVs (serpinD1 and MHC class III-complement C6) which allow to discriminate serum derived from different disease stages of OS (72).…”
Section: Evs As Biomarkers In Osmentioning
confidence: 99%
“…As far as EV-associated proteins are concerned, circulating levels of EV-associated TGF-β have been found to be increased in osteosarcoma patients, when compared to healthy control subjects (27). A proteomic investigation of circulating EVs in canine serum samples identified EV related proteins useful to distinguish serum of osteosarcoma from serum of healthy or fractured dogs (72). Furthermore, Brady et al identified two proteins associated with EVs (serpinD1 and MHC class III-complement C6) which allow to discriminate serum derived from different disease stages of OS (72).…”
Section: Evs As Biomarkers In Osmentioning
confidence: 99%
“…22 In osteosarcoma, exosomes have been shown to be related to migration, invasion, and tumor progression, but the complex interplay between osteosarcoma cells and macrophages has yet to be investigated. [23][24][25] Because a tumor-promoting microenvironment contains M2 macrophages, and M2 macrophages are linked to poor outcomes in patients with osteosarcoma lung metastases, we compared the extracellular communications between metastatic and non-metastatic osteosarcoma cells and alveolar macrophages. It was our hypothesis that metastatic osteosarcoma cells help to create a tumor-permissive environment by exosomal communication.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are no published studies specifically describing cancer detection using nucleosomes in dogs, several publications have described the utility of cfDNA (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%